English EMPOWERING SUSTAINABLE TOURISM SMES THROUGH DIGITAL TECHNOLOGY TO ENHANCE GLOBAL COMPETITIVENESS - Ilmawan, faiz Nuha (Soedirman Accounting, Auditing and Public Sector Journal, 2025)
This article explores strategies for empowering Micro, Small, and Medium Enterprises (MSMEs) in sustainable tourism by leveraging digital technology to enhance global competitiveness. Using the case study of DATABAJO CAFFEE in Labuan Bajo, this study analyzes how the integration of local identity with digital marketing and international collaboration, such as through the International Community Service ICSEMA 2025, can overcome resource limitations and market access. The findings show that digitalization not only increases market reach but also strengthens the commitment to sustainability and empowerment of local farmers. The main conclusion is that the synergy between local uniqueness, the use of technology, and the support of the global community constitutes a strategic model for tourism MSMEs to achieve global competitiveness while preserving their cultural values.